Papillon-Lefevre Syndrome: Report of two cases in the same family - Arzu Yıldırım Bicer; İlkay Peker; Oguzhan Demirel (Cumhuriyet University, 2012)
Papillon-Lefevre syndrome (PLS) is a rare autosomal recessive disorder characterized by the association of palmoplantar hyperkeratosis and premature loss of both deciduous and permanent  teeth. Two siblings (29-years-old female and 36-years-old male) with PLS who complained about early teeth loss, esthetic problems and difficulty during eating and speech refered to our clinic. After intraoral and radiologic examination we planned total prosthesis to first case's upper and lower jaw and partial prosthesis to second patient's upper and lower jaw. Patients' financial problem affected the treatment planning. This case report presents prosthodontic rehabilitation of two patients with PLS in the same family.